Quality and satisfaction with culinary education: evidence from Cyprus - Constanti, Panayiotis; Zopiatis, Anastasios; Theodossiou, Panayiotis (My University, 2014)
Culinary education has experienced remarkable growth in Cyprus in the past decade. Numerous institutions are offering a variety of related programs with the aim of adequately preparing the next generation of culinary professionals. Despite this unprecedented growth, many argue that a short-term opportunistic business mentality prevails. Driven by the profession’s celebrity status, institutions offering culinary-related education risk downgrading the quality of their portfolio. Adopting a uantitative methodology, the study set out to investigate industry professionals’ and educators’ perceptions of the quality and overall satisfaction with the current culinary education offerings. The findings inform and provide practical recommendations for those striving to improve the nature, identity, scope, and value of culinary education.
Keywords: Culinary education; Quality indicators; Satisfaction; Cyprus